دراسة الفعالية الحرارية للمبادل الحراري الأنبوبي - أيوب عيسى حسن (Tishreen University, 2019)
يمكن القول إن الهدف من تطوير صناعة المبادلات الحرارية هو زيادة فعّاليتها الطاقية وتحسين معامل انتقال الحرارة لها، إضافة إلى الحصول على أصغر وزن كتلي يلبي العملية الموكلة إلى هذه المبادلات، إلا أن ذلك يترافق بزيادة المقاومات الهيدروليكية وتغير في حالة الجريان، الأمر الذي يتطلب اختيار أفضل شروط لجريان الوسائط الناقلة للحرارة، وبالتالي تحسين عملية التبادل الحراري من وإلى سطوح المبادل. يتضمن هذا البحث دراسة تحليلية للتبادل الحراري على سطوح المبادلات الحرارية الأنبوبية وتوزع التيارات الحرارية عليها، وحساب الفعّالية الطافية فيها، بهدف الحصول على أفضل معامل للفعّالية الحرارية، مما ينعكس على اقتصادية المنشأة المستخدمة لهذه الأنواع من المبادلات، عن طريق ترشيد استهلاك الطاقة اللازمة لإنجاز عملية التبادل الحراري، والتوفير في مواد التصنيع وزمنه. The aim of developing thermal exchangers' production, it is fair to say, is to improve their energetic activity and heat transfer coefficient, as well as obtaining minimum mass weight suitable to carrying out the process linked to such exchanges. This requires choosing optimal conditions for heat conductors' stream. Therefore, the heat-exchange process from and into exchanging surfaces can be improved. This paper contains an analytical study of heat transfer from surfaces of Shell and tube heat exchangers, distribution of heating streams on them and an estimate of their energetic activity, in order to obtain maximum coefficient of energy. Thus, the economic installation using this sort of exchangers will gain further profit, through rationing the consumption of energy necessary to accomplish the heat exchange process, reduce the production materials' cost and save time.